Pola Komunikasi Ritual Purnama dan Tilem pada Umat Hindu di Kota Pekanbaru - Siagian, Dewi Radiatul Irabiah; Yozani, Ringgo Eldapi; Yazid, Tantri Puspita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Hindus in Pekanbaru City are migrants who come from various regions. Hindus in Pekanbaru City have a small number compared to other religions with a presentation of 0.02%. But this does not reduce their obedience in carrying out purnama and tilem rituals. This research uses a ritual perspective, where communication is not a process of message transmission but as a representation of shared beliefs. This research aims to describe the communication patterns of full moon and tilem rituals in Hindus in Pekanbaru City. The method used in this research is descriptive qualitative which focuses on observation and interview. The results showed that the communication of purnama and tilem rituals in Pekanbaru City was carried out with five series of processes, namely nganteb banten, puja trisandya, kramaning sembah, hening and doa, and dharma wacana. Hindus perform purnama and tilem rituals as a form of gratitude and devotion for all the blessings that have been given by Sang Hyang Widhi.